Investigation of audible carbon monoxide alarm ownership: Case study. Issue 1 (13th May 2014) - Kokkarinen, Noora; Shaw, Andy; Cullen, Jeff; Ortoneda Pedrola, Montserrat; Mason, Alex; Al-Shamma'a, Ahmed
Abstract : Purpose: – The purpose of this paper is to outline the level of audible carbon monoxide (CO) alarm ownership. In this particular paper the data collected by the fire and rescue services from West Midlands and Merseyside will be analysed, and discussed. Design/methodology/approach: – Research was conducted in two stages. Using the indices of multiple deprivation identified whether households in the top and bottom four areas owned an audible alarm. In stage two data loggers were placed into homes to take readings every minute for a total period of three days to three weeks. Findings: – There was a noticeable trend that deprived areas were less likely to own audible CO alarms than homes in non-deprived areas. All homes surveyed in stage two had CO levels >0 which further emphasises that anyone can be under health risk and that perhaps the maintenance of gas appliances and other sources is not being conducted at regular intervals. Social implications: – This paper aims to raise awareness regarding not only the symptoms during CO poisoning but also the ones that have been reported to occur after treatment. It will also disseminate information as to what areas have low alarm ownership and thus more at risk of poisoning. It is hoped that findings from papers such as this one will promote more stringent maintenance and replacement requirements for gas or solid fuel appliances. Originality/value: – Pilot study for the comparison of two English cities has not been conducted before and may lead to more studies of this kind.